2007
DOI: 10.1177/0731684406072538
|View full text |Cite
|
Sign up to set email alerts
|

Torsional Buckling of Multi-walled Carbon Nanotubes Subjected to Torsional Loads

Abstract: The torsional buckling of an individual multi-walled carbon nanotube under two different loading conditions is studied in this article. The multiple shell model is adopted and the effects of van der Waals forces between adjacent nanotubes are taken into account. An examination with an individual double-walled carbon nanotube shows that the effect of the change of interlayer spacing on the torsional buckling force can be neglected if only the innermost radius is larger than a certain value. Under this condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Due to their unique properties, a significant amount of research has been devoted to their synthesis, characterization, and applications [7][8][9][10]. In particular, the mechanical properties of CNTs, and their modification, have been the subject of numerous research studies [11][12][13][14][15]. For instance, Brieland-Shoultz et al [2] showed that the effective Young's modulus of CNT micropillars increased from 14.5 MPa for uncoated CNTs to 24.5 GPa with 51 nm Al 2 O 3 coating.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique properties, a significant amount of research has been devoted to their synthesis, characterization, and applications [7][8][9][10]. In particular, the mechanical properties of CNTs, and their modification, have been the subject of numerous research studies [11][12][13][14][15]. For instance, Brieland-Shoultz et al [2] showed that the effective Young's modulus of CNT micropillars increased from 14.5 MPa for uncoated CNTs to 24.5 GPa with 51 nm Al 2 O 3 coating.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier modelling efforts on MWCNTs via shell models towards torsional buckling with van der Waals interactions indicated interlayer slipping governed critical shear for thinwalled, large radii nanotubes, where the number of layers does not significantly impact behaviour. 130 This finding implies a potential limitation as well as a convenience for most composite applications today and in the near future, since polydisperse MWCNTs are currently the most readily available and affordable for scale-up targeting feasible materials and technology development in the short-term. Saha and Maiti generally support this outcome for MWCNTs from 2-6 layers thick, with extensive results on triple-walled CNTs.…”
Section: Carbon Nanotubesmentioning
confidence: 99%
“…Torsional buckling via shell model and MD simulations support a van der Waals interaction between layers in shear for double-walled CNTs128 and MWCNTs129 that strengthens the nanomaterial. Earlier modelling efforts on MWCNTs via shell models towards torsional buckling with van der Waals interactions indicated interlayer slipping governed critical shear for thin-walled, large radii nanotubes, where the number of layers does not significantly impact behaviour 130. This finding implies a potential limitation as well as a convenience for most composite applications today and in the near future, since polydisperse MWCNTs are currently the most readily available and affordable for scale-up targeting feasible materials and technology development in the short-term.…”
Section: One-dimensional Nanowires Nanotubes and Other Nanostructuresmentioning
confidence: 99%
“…In the analysis of single-walled carbon nanotubes (SWCNs), there are in the literature three-dimensional finite element models 46 for armchair, zigzag and chiral SWCNs, wherein the bonds between carbon atoms are considered as connecting load-carrying members, while the carbon atoms as joints of the members. To create the finite element (FE) models, nodes are placed at the locations of carbon atoms and the bonds between them are modeled using the three-dimensional elastic beam elements.…”
Section: Introductionmentioning
confidence: 99%